One Step Nucleic Acid Amplification (OSNA) Study in Indonesia - Samuel J Haryono; Lenny Sari; Sony Sugiharto; I Gusti Bagus Datasena; Raymond Mulyarahardja; . Rudianto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
ABSTRACTSentinel lymph node (SLN) is defined as the first of a few selected lymphatic nodes, into which lymphatic fluid from a primary tumor drains. Streamlined processing of sentinel lymph nodes (SLN) for detection of lymph node metastasis involves the able command over methodical blocks of SLN identification, surgical removal of SLN and SLN analysis. One Step Nucleic Acid Amplification (OSNA) method, which relies on CK19 mRNA expression to detect intraoperatively  lymph node metastases in breast cancer cases, emerged as a plausible alternative to the current gold standard that uses histopathological node analysis. Sixty selected axillary sentinel lymph nodes from thirty breast cancer patients. Sentinel lymph nodes were directly bi-halved after collection using customized lymph node cutting device (Sysmex), or scalpel. The first halves were subjected to histopathological examination and were stored in specimen containers containing fresh formaldehyde prior to processing. The adjacent halves were weighed to comply with the required mass by OSNA detection in the range of 50 – 600 mg and wrapped in clean foils for storage in -80°C prior to OSNA analysis. 60 SLNs were same diagnosis using both methods. 25 SLNs were negative and 25 SLNs were positive using both methods. 3 SLNs were positive on OSNA but negative on histology. Other 7 SLNs were negative on OSNA but positive on histology, and these 1 nodes contained only micrometastasis lesion. These results suggest that OSNA is a useful for detecting SLNs metastasis, but a copy number of CK19 might be an indepedent factor from prediction and prognosis of breast cancer.